2020
DOI: 10.1128/iai.00245-20
|View full text |Cite
|
Sign up to set email alerts
|

Small Noncoding RNA CjNC110 Influences Motility, Autoagglutination, AI-2 Localization, Hydrogen Peroxide Sensitivity, and Chicken Colonization in Campylobacter jejuni

Abstract: Small noncoding RNAs (ncRNAs) are involved in many important physiological functions in pathogenic microorganisms. Previous studies have identified the presence of noncoding RNAs in the major zoonotic pathogen Campylobacter jejuni; however, few have been functionally characterized to date. CjNC110 is a conserved ncRNA in C. jejuni, located downstream of the luxS gene, which is responsible for the production of the quorum sensing molecule autoinducer-2 (AI-2). In this study, we utilized strand specific high-thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 91 publications
(150 reference statements)
4
43
1
Order By: Relevance
“…At least 20 CJsORFs overlap annotated genes. Two CJsORFs overlap the infection-related sRNA CJnc110 (Kreuder et al, 2020). However, as regulatory targets for CJnc110 are so far not clear, CJnc110 might be a small mRNA, rather than a dual (regulatory and coding) function sRNA.…”
Section: Discussionmentioning
confidence: 99%
“…At least 20 CJsORFs overlap annotated genes. Two CJsORFs overlap the infection-related sRNA CJnc110 (Kreuder et al, 2020). However, as regulatory targets for CJnc110 are so far not clear, CJnc110 might be a small mRNA, rather than a dual (regulatory and coding) function sRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of CjNC110 resulted in decreased levels of extracellular AI-2, while intracellular levels of AI-2 were signi cantly increased. Results suggest that CjNC110 may participate in the transport of AI-2 in C. jejuni (Kreuder et al 2020). However, further research is needed to explain the details of quorum sensing machinery in C. jejuni.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, a small noncoding RNA, CjNC110, has been identified downstream of luxS in C. jejuni [ 93 ]. CjNC110-knockout mutants showed significantly increased accumulation of intracellular AI-2 compared to WT, while extracellular AI-2 levels were reduced.…”
Section: Introductionmentioning
confidence: 99%
“…CjNC110-knockout mutants showed significantly increased accumulation of intracellular AI-2 compared to WT, while extracellular AI-2 levels were reduced. This suggested that the CjNC110 RNA modulates AI-2 detection and export [ 93 ]. However, the role of this regulatory RNA in QS regulation and AI-2 export requires further investigation.…”
Section: Introductionmentioning
confidence: 99%